The potential roles of JAK/STAT signaling in the progression of osteoarthritis - Zhou, Qingluo; Ren, Qun; Jiao, Linhui; Huang, Jishang; Yi, Jun; Chen, Jincai; Lai, Jinliang; Ji, Guanglin; Zheng, Tiansheng (Frontiers in Endocrinology, 2022)
Osteoarthritis (OA) is an age-related chronic progressive degenerative disease that induces persistent pain and disabilities. The development of OA is a complex process, and the risk factors are various, including aging, genetics, trauma and altered biomechanics. Inflammation and immunity play an important role in the pathogenesis of OA. JAK/STAT pathway is one of the most prominent intracellular signaling pathways, regulating cell proliferation, differentiation, and apoptosis. Inflammatory factors can act as the initiators of JAK/STAT pathway, which is implicated in the pathophysiological activity of chondrocyte. In this article, we provide a review on the importance of JAK/STAT pathway in the pathological development of OA. Potentially, JAK/STAT pathway becomes a therapeutic target for managing OA.